Role of Computed Tomography in Diagnosis and Assessment of Disease Severity in Covid 19; Trends in Pakistan - M. Rizwan Asghar, Tayyiba Akhter, Khubaib Shahid, Namra Chaudhary, Imran Khan, Sohaib Amjad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To observe and compare relationship of High Resolution Computed Tomography severity score with presenting symptoms of COVID-19 positive patients in mild, moderate and severe disease and to analyze the trends of morbidity and mortality in Pakistan. Study Design: Retrospective Observational study Subjects and Methods: All OPD and admitted adult male and female patients serially presented to Fatima Memorial and Sir Ganga Ram Hospital Lahore with positive COVID PCR test or clinical symptoms were included in the study. These patients were classified in three groups; Group I: Mild disease, i.e. symptomatic patients who didn’t need hospital admission or oxygen support. Group II: Moderate disease, i.e. patients having oxygen saturation more than 90% & needing oxygen support at times, and Group III: severe disease, i.e. patients needing hospital admission or ventilator support and having oxygen saturation less than 90%. High resolution chest CT scan was the approach in all cases. CT severity score was used to assess the severity of lung parenchymal involvement by COVID-19 on all the HRCT. Data collected was entered and analysis made using SPSS v 25. Results: Total number of patients were 200(100%) with age ranging from 14-85 years and mean age was 49.5+ 5 years, out of which 135(67%) were males and 65(32%) were females with male to female ratio 2:1. HRCT scans of all patients were done with COVID PCR test positive in 146(73%) patients. Group I had 98(49%) patients, 87(43.5%) patients were included in Group II and 15(7.5%) patients in Group III. Oxygen was required in 78(39%) patients from group II and 14(7%) patients from severe disease required ventilator. Conclusion: Our research work presented the trends of CT severity scoring having positive correlation to clinical symptoms of patients. Moreover, most of the patients in our country were having mild and moderate disease and only 7% patients showed severe disease symptoms and CT scoring in our study. Out of those severe disease patients, mortality was only 1% as compared to 2.89% mortality reported in Iran.